Anmeldelser - Maegaard, Jan (Danish Yearbook of Musicology, 1998)
Review of: John C. Crawford and Dorothy L. Crawford: Expressionism in Twentieth Century Music. Indiana University Press, Bloomington & Indianapolis 1993.